Discovery and characterization of thermophilic limonene‐1, 2‐epoxide hydrolases from hot spring metagenomic libraries. (16th June 2015) - Ferrandi, Erica Elisa; Sayer, Christopher; Isupov, Michail N.; Annovazzi, Celeste; Marchesi, Carlotta; Iacobone, Gianluca; Peng, Xu; Bonch‐Osmolovskaya, Elizaveta; Wohlgemuth, Roland; Littlechild, Jennifer A.; Monti, Daniela
<x xml:space="preserve">Abstract</x> The epoxide hydrolases (EHs) represent an attractive option for the synthesis of chiral epoxides and 1, 2‐diols which are valuable building blocks for the synthesis of several pharmaceutical compounds. A metagenomic approach has been used to identify two new members of the atypical EH limonene‐1, 2‐epoxide hydrolase (LEH) family of enzymes. These two LEHs (Tomsk‐LEH and CH55‐LEH) show EH activities towards different epoxide substrates, differing in most cases from those previously identified for Rhodococcus erythropolis (Re‐LEH) in terms of stereoselectivity. Tomsk‐LEH and CH55‐LEH, both from thermophilic sources, have higher optimal temperatures and apparent melting temperatures than Re‐LEH. The new LEH enzymes have been crystallized and their structures solved to high resolution in the native form and in complex with the inhibitor valpromide for Tomsk‐LEH and poly(ethylene glycol) for CH55‐LEH. The structural analysis has provided insights into the LEH mechanism, substrate specificity and stereoselectivity of these new LEH enzymes, which has been supported by mutagenesis studies. Database The atomic coordinates and structure factors of the crystal structures have been deposited in the Protein Data Bank with the codes 5AIF (Tomsk‐LEH native structure), 5AIG (Tomsk‐LEH valpromide complex), 5AIH (CH55‐LEH native structure) and 5AII (CH55‐LEH PEG complex). Nucleotide sequence data are available in the GenBank databases under the accession numbers KP765711 (Tomsk‐LEH) and KP765710 (CH55‐LEH).